2008
DOI: 10.1002/pmj.20069
|View full text |Cite
|
Sign up to set email alerts
|

Value Stream Mapping in Project Management: A Case Study

Abstract: This article describes the application of value stream mapping to analyze and redesign the way of managing the materials procurement stage of a project. A framework based on integrated definition (IDEF) methodology, the stream analysis approach, activity‐based costing, and discrete event simulation is presented. The stream analysis approach is used to analyze, diagnose, and manage process changes represented using an IDEF model. A dynamic simulation is used to evaluate the impact of the changes considered, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(18 reference statements)
0
6
0
1
Order By: Relevance
“…Abdulmalek and Rajgopal (2007) have described a case where VSM and other lean principles are adopted for the process sector for application at a large integrated steel mill. Bevilacqua et al (2008) have described the application of VSM for analysing and redesigning the ways of managing the material procurement stage of a project. Seth et al (2008) have identified and addressed various wastes in the supply chain of the edible cotton seed oil industry using VSM approach for the improvement of productivity and capacity utilization in the Indian context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdulmalek and Rajgopal (2007) have described a case where VSM and other lean principles are adopted for the process sector for application at a large integrated steel mill. Bevilacqua et al (2008) have described the application of VSM for analysing and redesigning the ways of managing the material procurement stage of a project. Seth et al (2008) have identified and addressed various wastes in the supply chain of the edible cotton seed oil industry using VSM approach for the improvement of productivity and capacity utilization in the Indian context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although VSM is mainly used in manufacturing sector (Seth and Gupta, 2005; Chen et al , 2010; Lacerda et al , 2016), recently it has some service sector applications especially in health services (Snyder et al , 2005; Lummus et al , 2006; Henrique et al , 2016; Camgöz-Akdağ et al , 2017). There are some other service sector application examples, such as sales (Barber and Tietje, 2008), project management (Bevilacqua et al , 2008), supply chain (Arbulu et al , 2003) and office services (Chen and Cox, 2012). Singh et al (2011) and Dal Forno et al (2014) presented a comprehensive review and classification of literature on VSM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Se tratando dos aspectos pelo qual a teoria do VSM deve melhorar a fim de torná-lo uma ferramenta de referência, nem todos os esforços da implantação da ferramenta são de simples execução, pois Bevilacqua et al (2008) relata o aumento dos custos durante o projeto devido a necessidade de atenção das mudanças a serem implementadas em um caso de reengenharia para projetos de EPC (Engineering, Procurement and Construction), com um retorno estimado de 4 anos enquanto que Kocakulah e Upson (2005) citam um VPL (Valor Presente Líquido) negativo obtido em um projeto de VSM para o projeto de um sistema integrado para controle de atendimento de pacientes. No estudo de caso de Serrano et al (2008) em múltiplas empresas foi verificado que a implementação do fluxo de produção enxuto pode ser muito exigente para empresas que possuem poucos recursos enquanto que Wee e Wu (2009) recomendam precaução no estudo de caso realizado na Ford Motor Company, já que sua implementação poderia ser demorada e cara.…”
Section: Considerações Finaisunclassified